Diffusion tensor imaging is associated with motor outcomes of very preterm born children at 11 years of age - Katri Lahti (WILEY, 2022)
Aim
Very preterm children born <32 weeks of gestation are at risk for motor difficulties such as cerebral palsy and developmental coordination disorder. This study explores the association between diffusion tensor imaging metrics at term and motor outcomes at 11 years of age.
Methods
A cohort of 37 very preterm infants (mean gestational age 29 4/7, SD 2 0/7) born in 2004-2006 in Turku University Hospital underwent diffusion tensor imaging at term. A region of interest analysis of fractional anisotropy and mean diffusivity was performed. Motor outcomes at 11 years of age were measured with the Movement Assessment Battery for Children - Second Edition.
Results
The diffusion metrics of the corpus callosum (genu P = .005, splenium P = .049), the left corona radiata (P = .035) and the right optic radiation (P = .017) were related to later motor performance. Mean diffusivity decreased and fractional anisotropy increased in proportion to the improving performance.
Conclusion
The diffusion metrics of the genu and splenium of the corpus callosum, the left corona radiata and the right optic radiation at term were associated with motor skills at 11 years of age. Diffusion tensor imaging should be further studied as a potential tool in recognising children at risk for motor impairment.